2018
DOI: 10.1186/s13059-018-1491-4
|View full text |Cite
|
Sign up to set email alerts
|

Linking the International Wheat Genome Sequencing Consortium bread wheat reference genome sequence to wheat genetic and phenomic data

Abstract: The Wheat@URGI portal has been developed to provide the international community of researchers and breeders with access to the bread wheat reference genome sequence produced by the International Wheat Genome Sequencing Consortium. Genome browsers, BLAST, and InterMine tools have been established for in-depth exploration of the genome sequence together with additional linked datasets including physical maps, sequence variations, gene expression, and genetic and phenomic data from other international collaborati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(165 citation statements)
references
References 34 publications
(36 reference statements)
3
161
0
1
Order By: Relevance
“…For instance, each DNA TEs (TIRs, MITEs and Helitrons) covered almost the same percentage of the genome with 0.51, 0.72 and 0.72 %, respectively. These coverage patterns are in accordance with most plant genomes that had TEs identification projects(Du et al, 2010;Andorf et al, 2015;Badouin et al, 2017;Alaux et al, 2018).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…For instance, each DNA TEs (TIRs, MITEs and Helitrons) covered almost the same percentage of the genome with 0.51, 0.72 and 0.72 %, respectively. These coverage patterns are in accordance with most plant genomes that had TEs identification projects(Du et al, 2010;Andorf et al, 2015;Badouin et al, 2017;Alaux et al, 2018).…”
supporting
confidence: 82%
“…However, in the past years, TEs discovery and annotation for the main crops have been emerging with diverse results of coverage, complexity and accuracy. For instance, by using the CLARITE software on the IWGSC RefSeq v1.0 genome assembly, Alaux et al (2018) found over 5 million elements from all types of TEs in wheat. On the other hand, maize repeat elements were annotated with the Ensembl Genomes repeat feature pipeline which comprised the discovery of low complexity regions (Dust) (Morgulis et al, 2006), tandem repeat (TRF) (Benson et al, 1999) and complex repeats (RepeatMasker) (Smit et al, 1996) but lacking on TEs classes and types categorization (Andorf et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This led to 68 958 SNP markers available for subsequent analyses. Markers were physically mapped on the wheat genome refSeq v1.0 (IWGSC et al ., ) accessible at https://urgi.versailles.inra.fr/jbrowseiwgsc/gmod_jbrowse (Alaux et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Although the genomes of grassland plant species are large and will require a large amount of sequencing capacity, some reference genomes are already available for such species (e.g., red clover [114,115], perennial ryegrass [116]), and Italian ryegrass [117], which can help in assembling additional genomes with low coverage data. Furthermore, pangenomic information is becoming available for crop species with similarly large genomes, such as wheat, thanks to the joint efforts of international consortia (e.g., the International Wheat Genome Sequencing Consortium, [118]).…”
Section: Whole Genome Re-sequencingmentioning
confidence: 99%